Survival, Disability Rights, and Solidarity: Advancing Cyberprotest Rhetoric through Disability March - Mann, Benjamin W. (Disability Studies Quarterly, 2018)
Disability March (DM) was an online contingent of the 2017 Women's March on Washington which allowed protestors who could not attend physical marches due to disabilities to create profiles and descriptions on the website disabilitymarch.com. In this thematic analysis of the 2,251 profiles created through DM, I found emergent themes related to disability disclosure, support for broad health care coverage, support for human rights, and opposition to the new political administration. Comments supporting these themes demonstrated that DM functioned as a unique form of cyberprotest that upheld disabled perspectives through solidarity. This study demonstrates that disability cyberprotest movements like DM may promote disabled individuals within broader protest discourse and contemporary policy issues that are often essential to the survival and well-being of marginalized individuals.